Entrepreneurship and Innovation in E-Business - Hasan, Maruf; Ui, Harris (Advances in Social Sciences Research Journal, 2016)
The fast growth and business successes of eBay, Amazon.com, priceline.com, etc. and the bankruptcy of numerous dot.com companies worldwide in the late 1990s has held potent management implications for IT innovation and entrepreneurial organizations worldwide. Entrepreneurship and innovation are emerging disciplines for proactively responding to changes in the e-commerce world. This paper explores the synergies between entrepreneurship and innovation and investigates their roles in organisational development in general and dot.com companies in particular.